Bone Mineral Density in the Hip Joint - Yoshida, Kenji; Higuchi, Fujio; Inoue, Akio; Asakura, Toshiaki; Narita, Syugo (Orthopedics & Traumatology, 1994)
Bone mineral density of the hip joint was measured by dual energy x-ray absorptiometry. 134 hip joints were studied by Lunar DPX. Fifty cases had OA, 12 cases had RA, 5 cases had ANF, and 10 cases were normal hips. There was a correlation between OA and normal hip BMD at the neck. BMD of the acetabular load-bearing area of OA was significantly higher density, and that of BMD of RA was lower density. The BMD of hip joint was useful in determining the surgucal method to be used.